A preliminary study on post-occupancy evaluation of four office buildings in the UK based on the Analytic Hierarchy Process. (2nd October 2018) - Middlehurst, Gary; Yao, Runming; Jiang, Lai; Deng, Jie; Clements-Croome, Derek; Adams, George
ABSTRACT: There is a lack of a systematic decision-making criterion to select appropriate indicators for Post-Occupancy Evaluation (POE) analysis due to the fact that significant levels of various POE determinants are indeterminate. The present work aims to identify the degree of importance of a set of POE determinants based on Analytic Hierarchy Process (AHP). A case study of POE for four office buildings in the UK has been conducted using the AHP to ascertain the significance levels of three main factors identified, namely, Indoor Environment Quality (IEQ), Occupants' Performance (OP) and Workplace Quality (WQ) as well as three groups of sub-factors affiliated to the main factors based on questionnaire surveys of the building occupants. The results show that the priority factors of the three main evaluation metrics, IEQ, OP, WQ are 0.595, 0.183 and 0.222, respectively, indicating that of these three factors the IEQ is the paramount factor in relation to the POE level of the office buildings. Moreover, the global priorities of all sub-factors linked to the main factors are obtained, providing a strategy reference of choosing indicators as per the priorities for a continuing POE in the further survey and measurement.